Estimates of regression parameters of random fields. II. - Leonenko , N. N.; Le Fe Do, (Ukrains’kyi Matematychnyi Zhurnal, 1992)
We investigate asymptotic properties of modified least-square estimators (MLSE) of regression parameters of random fields.